EUCLEA CRISPA: REVIEW OF ITS BOTANY, ETHNOMEDICINAL USES, AND PHARMACOLOGICAL PROPERTIES - Maroyi, Alfred (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Euclea crispa is widely used as herbal medicine in southern Africa. This study was aimed at reviewing the botany, ethnomedicinal uses, and validated pharmacological properties of E. crispa. The literature search for information on ethnomedicinal uses and pharmacological activities of E. crispa was undertaken using databases such as web of science, BMC, science direct, elsevier, scopus, PubMed, and scielo. Other relevant literature sources included books, book chapters, websites, theses, conference papers, and other scientific publications. The extensive literature survey revealed that the bark, fruits, leaves, and roots of E. crispa are commonly used as herbal medicines for wounds, constipation, cough, stomach disorders, epilepsy, rheumatism, and diabetes. Pharmacological studies on E. crispa indicate that the species has amyloid Î²-peptide lowering effects, antibacterial, antidiarrheal, antifungal, and cell membrane disruption activities. E. crispa should be subjected to further scientific evaluations aimed at elucidating its chemical, pharmacological, and toxicological properties. Such detailed research should also include experimental animal studies, randomized clinical trials, and target-organ toxicity studies involving E. crispa extracts and its derivatives.